2010
DOI: 10.1161/atvbaha.109.194530
|View full text |Cite
|
Sign up to set email alerts
|

SERCA2b Activity Is Regulated by Cyclophilins in Human Platelets

Abstract: Objective-The role of cyclophilins (chaperones that are widely expressed in different cell types, including human platelets) was explored in sarcoendoplasmic calcium (Ca 2ϩ ) adenosine triphosphatase (SERCA) activity. Methods and Results-Cyclophilin inhibition by cyclosporin A (CsA) evoked a time-and concentration-dependent reduction of Ca 2ϩ uptake by SERCA2b. However, other Ca 2ϩ -adenosine triphosphatases expressed in platelets, such as SERCA3 and plasma membrane Ca 2ϩ adenosine triphophatase, remained unal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…However, we also found colocalization of SERCA2b and STIM1 in murine platelets, providing strong evidence that SERCA2b also belongs to the protein complex STIM1/CyPA ( Figure 4F). Interaction of SERCA2b and STIM1 takes place independently of CyPA, suggesting a role of STIM1 in the regulation of SERCA2b, as proposed previously by Rosado et al 18 CyPA deficiency leads to defective platelet adhesion and thrombus formation under flow conditions ( Figure 1F-G). To determine whether STIM1 phosphorylation is important for cell adhesion, we made use of a platelet model cell line called A5-CHO, a specific CHO cell that stably overexpresses human integrin ␣ IIb ␤ 3 , 49 and allowed these cells to spread on fibrinogen.…”
Section: Lack Of Cypa Prevents Phosphorylation Of Stim1supporting
confidence: 81%
See 4 more Smart Citations
“…However, we also found colocalization of SERCA2b and STIM1 in murine platelets, providing strong evidence that SERCA2b also belongs to the protein complex STIM1/CyPA ( Figure 4F). Interaction of SERCA2b and STIM1 takes place independently of CyPA, suggesting a role of STIM1 in the regulation of SERCA2b, as proposed previously by Rosado et al 18 CyPA deficiency leads to defective platelet adhesion and thrombus formation under flow conditions ( Figure 1F-G). To determine whether STIM1 phosphorylation is important for cell adhesion, we made use of a platelet model cell line called A5-CHO, a specific CHO cell that stably overexpresses human integrin ␣ IIb ␤ 3 , 49 and allowed these cells to spread on fibrinogen.…”
Section: Lack Of Cypa Prevents Phosphorylation Of Stim1supporting
confidence: 81%
“…18 In the present study, immunoprecipitation studies also identified colocalization of CyPA and SERCA2b in murine platelets, suggesting that CyPA is also responsible for the regulation of SERCA2b in murine platelets ( Figure 4E). On thrombin stimulation, colocalization of these proteins decreased, whereas in mutant platelets, complex formation of SERCA2b and CyPA could not take place because of CyPA deficiency ( Figure 4E).…”
Section: Lack Of Cypa Prevents Phosphorylation Of Stim1supporting
confidence: 73%
See 3 more Smart Citations